Ethylene glycol and ethanol oxidation on spinel ni-co oxides in alkaline - Xu, Zhichuan J. (2019)
This article presents a systematic study on the composition dependence of Ni-Co oxides (NCOs) on their electrocatalytic activities toward ethylene glycol (EG) and ethanol (EtOH) oxidation. NCO electrodes were prepared by co-electrodeposition method followed by annealing in air. The atomic ratios of Ni / (Ni + Co) (Ni content) in NCOs were controlled by adjusting the concentration ratio of Ni and Co precursors. As the Ni content increased, the phase of materials changed from the spinel to the mixture of spinel and rock salt. The electrocatalytic activities of these NCOs toward EG and EtOH oxidation were investigated by cyclic voltammetry, differential pulse voltammetry, multi-step chronoamperometry, and electrochemical impedance spectroscopy techniques. It was found that the performance of NCOs for EG and EtOH oxidation exhibited a firstly-increase-then-decrease trend with the increase of Ni content and the best performance was found at 46% Ni. The presence of Ni probably can facilitate EG and EtOH oxidation. Increasing the concentration of reactants or pH can improve the reaction rates. The products from EG and EtOH oxidation were analyzed by nuclear magnetic resonance, which indicated that the oxidation reaction was a process from hydroxyl group to carboxyl group.